Through Their Eyes: Unveiling Stigma Surrounding Mental Illness from the Lived Experiences of Patients - Sonker, Saloni (Indian journal of criminology, 2024)
The present study aimed to investigate how individuals having mental illness perceive and respond to stigmatizing beliefs held by community members towards mental illness, as well as to explore the factors influencing the stigma encountered by individuals having mental illness. A quantitative survey method was employed for this purpose. A total of sixty-one participants participated in the study, including thirty-six females and thirty-five males. For the study, pre-existing English- language scales were adapted and translated into Hindi to ensure participant comprehension. These measures comprised the Internalized Stigma of Mental Illness (ISMI) scale, the Multidimensional Scale for Perceived Social Support (MSPSS), and demographic details form. The study's findings revealed that internalized stigma experiences are mitigated by a range of factors including social support, demographic variables, and clinical characteristics. Age and the length of the illness were the main variables influencing internalized stigma. The study concludes that different clinical and demographic groups should have carefully tailored psychological interventions, designed specifically to fit their needs. In addition, the fact that patients are hesitant to discuss their experiences due to fear of stigmatization highlights how important it is to overcome negative beliefs and attitudes.